Genetic Divergence Studies for Yield, Yield Attributes and Quality Traits in Okra [Abelmoschus esculentus (L.)] - Neeraja, S.; Srinivas, J.; Joshi, Veena; Nikhil, B. Sai Krishna; Sathish, G. (International Journal of Bio-resource and Stress Management, 2025)
The present experiment was conducted during October, 2021 to January, 2022 in the department of Vegetable Science, College of Horticulture, Mojerla, Wanapathy District, Sri Konda Laxman Telangana State Horticultural, University, Mulugu, Siddipet, Telangana, (509 382), India on the genetic divergence studies in Okra (Abelmoschus esculentus L.) genotypes. 37 okra diverse okra genotypes were evaluated in a randomized block design (RBD) with three replications using various yield attributes. The cluster VI showed maximum intra-cluster distance (752.33) followed by cluster V (491.19) and Clusters IV (434.85). The inter-cluster D2 values of the nine clusters recorded that the highest inter-cluster generalized distance (5966.95) was between cluster VIII and cluster IX. The per cent contribution of different characters towards genetic divergence of genotypes of cluster IX registered maximum fruit length (14.35 cm). Fruit diameter exhibited maximum in cluster II (1.95 cm). Early days to first picking were recorded in cluster VI (42.05 days). Number of fruits plant-1 was highest in cluster IX (52.90) and lowest in cluster II (18.53). Fruit yield plant-1 was recorded maximum in cluster IX (0.44 kg), while it was minimum in cluster VIII (0.16 kg) showed the highest yield contributing characters towards total diversity among the genotypes, IC33823, IC42490, EC329422, IC42484 and IC42470 are more genetically diverse among the genotypes and can be used in hybridization programme, for obtaining superior and desirable recombinants.